Cognitive impairment - Ahmad, Hafandi (Universiti Putra Malaysia Press, 2016)
Cognitive ability is directly related to physiological condition of the brain. Apart from ageing, cognition can be affected with use of chemical and organic compounds. This art form is a physical portrayal of multiple treatments on cognitive function in rats. The footprints and paths of the rats are depicted in colours that represent different cognitive conditions.